Desorption studies for methylene blue dye removal by kaolinite / Puteri Balqis Awatif Abdul Ghani, Ruhaida Rusmin and Izzan Salwana Izman - Abdul Ghani, Puteri Balqis Awatif; Rusmin, Ruhaida; Izman, Izzan Salwana (Universiti Teknologi MARA, 2021)
In wastewater treatment, the reusability of an adsorbent strongly relies on the feasibility of contaminant desorption from the spent adsorbent. This research aims to investigate the Methylene Blue (MB) release from the spent kaolinite clay mineral against a variety of desorbing eluent in an aqueous solution. Malaysia's kaolinite was characterized using Scanning Electron Microscopy (SEM), surface area analysis, and Fourier Transform Infrared (FTIR) Spectroscopy. The MB desorption was performed using eluents of distilled water, solutions of HCl, NaOH, and NaCl (0.01 M and 0.1 M), and ethanol: water mixtures (30:70, 50:50, and 70:30 v/v ratios). It was found that the MB desorption only occurs in 0.1 M NaOH (pH 12.7). A 4.2% MB desorption was recorded in 1 hour and was increased to 19.5% within 24 hours desorption time. The pH change measurement also reveals the favorability for highly alkaline conditions for MB desorption. The overall finding indicates that the MB retention towards kaolinite is strong, and its adsorption occurs via electrostatic and hydrophobic interaction, as suggested by the FTIR analysis. Kaolinite is a good scavenger for removing the MB dye from contaminated water but requires a strong eluent in the desorption process for its future reusability process.